Adverse Selection in the Wholesale Used Car Market - Genesove, David (Journal of Political Economy, 1993)
This paper presents an empirical investigation of adverse selection in the wholesale used car market. New car dealers (who sell both new and used cars) differ from used car dealers (who sell only used cars) in the propensity to sell trade-ins on the wholesale market. Models of adverse selection suggest that the dealer type that sells a higher proportion of its trade-ins on the wholesale market will sell, on average, cars of higher quality and receive in return a higher price. A survey of dealers' wholesale behavior and prices collected at a wholesale auction are used to test this prediction. I find weak evidence for adverse selection.